PENGEMBANGAN MEDIA PEMBELAJARAN KARTU DOMINO UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA KELAS VI DI SDN BOJONGMANGU 01 - Santika, Dewi; Ira Restu Kurnia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the lack of learning media which resulted in low understanding of concepts. This research aims to increase understanding of science concepts for class VI SDN Bojongmangu 01. The research used is Research and Development (R&D) with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, evaluation. The results show that the domino card media was declared "Very Valid" for testing as proven by the validator results, namely obtaining a percentage of 94% media experts, 97.5% language experts, and 92% material experts. The response of teachers and students in small group and large group trials on domino card media was 91% teacher response, 95.5% for small groups and 96.5% for large groups declared "Very Practical" as a science learning media. The domino card media product in the N-Gain score test was to increase understanding of science concepts from the pretest and posttest results which obtained a significance of 0.65 with "medium" criteria. It can be concluded that domino card media can improve understanding of class VI science concepts.